SISTEM PENDINGINAN ALTERNATOR PADA PEMBANGKIT LISTRIK TENAGA UAP (PLTU) ASAM-ASAM - Syarifil anwar (AL-ULUM: JURNAL SAINS DAN TEKNOLOGI, 2016)
AC generator which is also called the alternator is a rotating electrical machine which can transform mechanical energy into electrical energy through the magnetic field based on electromagnetic principles.The mechanical energy is obtained to play comes from the AC generator or turbine prime movers.Power Plant Asam-asam is the powerhouse that has an installed capacity of 260 MW (4 x 65 Mw) which is expected to meet the requirement of power supply in the region of South Kalimantan and Central Kalimantan. In keeping operations on one or all of the electricity power generation equipment can run smoothly and well, it must be held maintenance and monitoring good and accurate.Alternator or generator AC at power plants work continuously or 24-hour turnaround every day that cause heat to the alternator or generator AC. To keep the alternator is not experiencing excessive heat, it is necessary water cooling system, so that the alternator can last a long time and no disruption in the operation.